To the question of combating corruption in the procurement of medical preparations - Марчук, Макар Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In the article investigational peculiarities of legal regulation of combating corruption in the implementation of procurement medical products in Ukraine and defined the real state of this phenomenon. Detected the reasons of the influence the level of corruption in the health sector, including the purchase of medicines. Also, analyzed the efficiency of already implemented steps toward modernizing the state anticorruption policy in this area. Found out problematic aspects of initiated measures. Highlight priority areas (together with necessary measures) aimed at improving the fight against corruption at the national level. The problem of combating corruption in the implementation of procurement medical products particularly acute in the years 2014-2015, when in Ukraine has increased inflation and spread cases of price manipulation on these drugs, and the corresponding effective regulation, which would help it confront not been developed. In addition, to this day any by-law on the transfer of purchasing medicines and vaccines to international organizations is not developed. Also: – no approved drugs for procurement nomenclature; – not calculated the exact number medical products that will be purchased even by the end of 2016 year. The mentioned caused corruption system, which was built in Ukraine in such a way, for example, that medicines bought sometimes ten times more expensive. Falsification cost is usually held in offshore areas where fictitious company sold products to each other, and then imported into Ukraine as if very expensive purchased abroad. The transition to the new system of procurement caused temporary delays supply of medicines and vaccines to pharmacies and hospitals, prompting outrage from the community. In order to ensure greater financial affordability of medical products for citizens planned: – the phased implementing a system the reimbursement of essential medicines (partial or complete reimbursement of the cost of medicinal product through the national system of health insurance); – simplification of market entry for qualitative of medicines (deregulation of the pharmaceutical market). Is to simplify the registration of medicinal products, that have undergone registration in countries with strict regulatory jurisdiction; – reforming the regulation of prices for medicines (the state will regulate prices only for medicines, that are purchased or reimbursed by the budget (public) funds. Regulation of prices in the free market will take place on the principles of free competition). In our opinion, to reduce the amount of crime and corruption in the implementation of procurement medical products is advisable to implement such measures: Cabinet of Ministers of Ukraine: - bolish normative and legal acts, that dictate to customers the choice of certain medications, як предметів закупівлі, adopting instead a normative document, which will be fully regulated the issue features defining the subject of procurement in the health sector (range of medications) with incorporates international standards; - implement a new model of health care financing on the basis of health insurance; - accept the new resolution of the Cabinet of Ministers of Ukraine «About the reference pricing on medical products» in order to improve declaration of change of wholesale prices excluding value added tax; Ministry of Health: - retrain national preparations according to WHO standards; - to introduce for mandatory application open to public registers medications, registered in the European Union and approved for use with the reference prices; - conduct a European adaptation of clinical protocols instead of writing sampling protocols under the Ministry of health selected medicines; - view the national list of essential vital medications and medical supplies with the inclusion of its proven effective and safe drugs.